Haemolytic-uraemic syndrome presenting as an acute abdomen. - Lamont, P. M. (BMJ Group, 1987)
Haemolytic-uraemic syndrome (HUS) may present with symptoms and signs suggestive of an acute surgical condition of the abdomen. The patient described was admitted with clinical features sufficient to warrant operation but later proved to have HUS.